Carbon Emission Simulation at the Slamet Riyadi Three-Way Intersection in Samarinda City Using Urban Mobility Simulation - Arsan Kumala Jaya; Fara Triadi; Abdullah Hanif (Program Studi Teknik Komputer, 2025)
This study uses Simulation Urban Mobility (SUMO) to simulate carbon emissions at the Slamet Riyadi Samarinda intersection. One of the big cities in Indonesia, Samarinda, faces major problems related to increasing traffic volume and its impact on air quality, especially carbon emissions. This simulation uses various traffic parameters, such as vehicle density, red light duration, and vehicle type. The purpose of this simulation is to evaluate the level of carbon emissions produced by vehicles passing through the intersection. The simulation begins by collecting traffic data and then converting it into an XML file that can be read by SUMO. This XML file contains information about traffic parameters, road networks, and vehicles. According to the simulation results, trucks contributed the most emissions per vehicle, with a total emission of almost 18,500 grams of CO₂ per hour. Traffic scenarios under real-world conditions were simulated using the SUMO tool with HBEFA-based emission models.. This study is expected to provide a clearer picture of the impact of traffic on the environment as well as recommendations for more effective traffic management strategies to reduce carbon emissions in Samarinda City.